Breaking the bottlenecks in anti-tumor angiogenic therapy: targeting vasculogenic mimicry with natural products and traditional Chinese medicine - Liu, Huan; Zhang, Yuan; Lv, Xuanyu; Ding, Xueying; Liao, Wenlu; Sun, Weifang; Zhang, Yanan; Song, Chunyan; Tang, Yong (Frontiers in Pharmacology, 2025)
Cancer, as a major public health problem threatening human health, poses significant challenges in clinical management due to its high invasiveness, metastatic potential, and therapeutic resistance. Vasculogenic mimicry (VM) is a vascular-like structure autonomously formed by highly plastic tumor cells and has been shown to be one of the significant factors influencing the progression, metastasis, and therapeutic resistance of malignant tumors. Unlike conventional anti-angiogenic therapies that primarily target endothelial cell-mediated neovascularization, VM can facilitate the transport of oxygen and nutrients in the absence of endothelial cell participation. This unique mechanism limits the efficacy of current anti-angiogenic strategies and contributes to treatment failure and tumor recurrence. Consequently, the development of novel therapeutic strategies is of paramount importance. In recent years, accumulating evidence has demonstrated that natural products (NPs) and traditional Chinese medicine (TCM), owing to their multi-component and multi-target properties, exhibit unique advantages and significant potential in inhibiting VM formation. This review systematically summarizes recent advances in the application of NPs and TCM to inhibit VM, with a focus on their key mechanisms of action in regulating cell adhesion molecules, extracellular matrix remodeling, epithelial-mesenchymal transition, cancer stemness, hypoxia adaptation, and ferroptosis. Furthermore, we summarize the anti-VM mechanisms of NPs and TCM in multiple malignant tumors such as lung cancer, liver cancer, breast cancer, and glioblastoma, and clarify their potential application prospects. These findings provide a theoretical foundation for developing VM-targeted therapies and promote the transformation and application of NPs and TCM in the field of anti-tumor VM.